2017
DOI: 10.1007/s13300-017-0321-0
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-effectiveness of Dulaglutide 1.5mg versus Exenatide QW for the Treatment of Patients with Type 2 Diabetes Mellitus in France

Abstract: IntroductionDulaglutide is a novel onceweekly administered glucagon-like peptide 1 receptor agonist (GLP-1 RA) for the management of type 2 diabetes mellitus (T2DM). The objective of this analysis was to estimate the cost-effectiveness of dulaglutide 1.5 mg versus exenatide QW for the management of T2DM in France.MethodsThe QuintilesIMS CORE Diabetes Model was used to estimate the expected lifetime direct medical costs and outcomes of T2DM from the perspective of the French National Health Service. In the abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…The Data Protection Commissioner of the data protection agency of the German Federal state Hesse endorses the data transmission, processing, and storage procedures for DA. DA has been used in other studies focusing on different outcomes in diabetes treatment [16][17][18] .…”
Section: Ims Disease Analyzer Databasementioning
confidence: 99%
“…The Data Protection Commissioner of the data protection agency of the German Federal state Hesse endorses the data transmission, processing, and storage procedures for DA. DA has been used in other studies focusing on different outcomes in diabetes treatment [16][17][18] .…”
Section: Ims Disease Analyzer Databasementioning
confidence: 99%
“…The results were not conclusive for the aGLP-1. 20,21,23,25,33,3566 Albiglutide appeared to be a more cost-effective option than sitagliptin, 35 but the results were the opposite when comparing the general subgroups to which these NIADs belonged (aGLP-1 versus iDPP-4). 20 Exenatide was a more cost-effective treatment than another analogue such as lixisenatide (ICER of €12,600/QALY), 36 but no conclusive results were obtained in comparison with other analogues such as liraglutide, 3641 or dulaglutide.…”
Section: Resultsmentioning
confidence: 97%
“…39,4749 Dulaglutide was dominant over liraglutide, 46 but contradictory results were obtained versus exenatide. 36,42…”
Section: Resultsmentioning
confidence: 99%
“…In a review of the literature, four economic analyses were identified comparing one GLP-1 receptor agonist with another. These studies were conducted in France [45], Italy [46], the UK [47], and Spain [48]. The diversity of methods and treatment alternatives used in these analyses prevented comparing the conclusions with those of the present study.…”
Section: Discussionmentioning
confidence: 99%